2020
DOI: 10.1002/jac5.1205
|View full text |Cite
|
Sign up to set email alerts
|

The impact of educational interventions on antibiotic prescribing for acute upper respiratory tract infections in the ambulatory care setting: A quasi‐experimental study

Abstract: Objective: To identify the proportion of viral acute upper respiratory tract infections (AURTI) inappropriately treated with antibiotics before and after the implementation of a multimodal outpatient antibiotic stewardship initiative in a real-world setting.Design: Pre-post, quasi-experimental study. Patients: Adult patients with a diagnosis of either acute bronchitis, influenza, unspecified viral infection, or unspecified AURTI who visited internal medicine (IM) or family medicine (FM) ambulatory care clinics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…6 Despite guidance from the CDC to establish outpatient ASPs, literature examining successful ASP interventions within primary care sites is limited; most studies target upper respiratory tract infections (URIs). [7][8][9][10][11][12] Furthermore, few efforts have targeted medical residents, an important target for ASPs in establishing good habits for antibiotic prescribing. [13][14][15] Although infectious diseases (ID) practitioners typically serve as ASP leaders in inpatient settings, this resource may be scarce in the outpatient setting.…”
mentioning
confidence: 99%
“…6 Despite guidance from the CDC to establish outpatient ASPs, literature examining successful ASP interventions within primary care sites is limited; most studies target upper respiratory tract infections (URIs). [7][8][9][10][11][12] Furthermore, few efforts have targeted medical residents, an important target for ASPs in establishing good habits for antibiotic prescribing. [13][14][15] Although infectious diseases (ID) practitioners typically serve as ASP leaders in inpatient settings, this resource may be scarce in the outpatient setting.…”
mentioning
confidence: 99%
“…21 Similarly, another study evaluated the effect of pharmacist educational intervention on the rate of antimicrobial prescribing in upper respiratory infections (acute bronchitis, influenza, unspecified viral infection, and URI). 23 The intervention was multimodal including creation and dissemination of guidelines/clinical pathways for the management of URI, roundtable discussions with providers outlining appropriate antimicrobial usage, and display of patient-facing antimicrobial commitment posters in clinics. As a result of educational intervention, a combined prescribing rate for internal medicine and family medicine clinic visits for these disease states demonstrated an absolute decrease from 17.2% to 13.1% (P = .02), with a relative decrease in inappropriate prescribing of 24% during the study period.…”
Section: Institutional Experiencementioning
confidence: 99%
“…As a result of educational intervention, a combined prescribing rate for internal medicine and family medicine clinic visits for these disease states demonstrated an absolute decrease from 17.2% to 13.1% (P = .02), with a relative decrease in inappropriate prescribing of 24% during the study period. 23…”
Section: Institutional Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Craddock et al 3 reported that 17.2 and 25.4% of viral acute upper respiratory tract infections (AURTI) were inappropriately treated with antibiotics at urban internal medicine (IM) and family medicine (FM) ambulatory care clinics, respectively. A previous study reported that, among 6136 patients with acute respiratory infections (ARIs), 2522 (41%) had diagnoses for which antibiotics are not indicated; moreover, 2106 (84%) patients were diagnosed as having a viral upper respiratory tract infection or bronchitis 4 .…”
Section: Introductionmentioning
confidence: 99%